(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. L’uso politico dell’etica confuciana nelle transizioni costituzionali. Una premessa sui primi casi di studio - 2. Il valore della tradizione: formazione individuale, conforto spirituale e proiezioni pubblicistiche- 3.Tra diritto e non diritto: una rappresentazione simbolica della pratica di governo - 4. Dal governo degli uomini al governo negli uomini: introiettare il senso della misura - 5. Profili possibili per l’evidenziazione della questione di genere nel pensiero confuciano: le forme e i tipi di un potere ancora maschile - 6. Incognite conclusive: dal merito di un’elaborazione inclusivistica e plurale al rischio di un confucianesimo fungibile per ogni istanza e perciò privo di contenuto. Risks and dynamics of reintegration of the individual private dimension into the public sphere. Recent researches on normative Confucian ethics ABSTRACT: If it seems substantially correct to deny a proper religious qualification for Confucianism, it does not mean that this kind of moral and legal teachings is irrelevant to shape a precise conception of human behavior, rites and relationships between citizenship and government. Finally adequately considered by the Western juridical doctrine, Confucianism and the Confucian scholars are now experiencing an uncritical acclaim too much vague to clarify rigorously the core sense of the first Confucian moral positioning. Some of the finest and the most exhaustive contemporary researches about Confucianism are now going back to the roots of the Chinese political thought, reaching new and more refined interpretations of the same ancient sources. This current renewal could be an excellent opportunity even for the European and Western jurists: the possibility to release an enduring phase of confrontation between the Continental and the Asian constitutionalism.